Cardiac GPCR–Mediated EGFR Transactivation: Impact and Therapeutic Implications. Issue 1 (July 2017) - Grisanti, Laurel A.; Guo, Shuchi; Tilley, Douglas G.
Abstract : Abstract: G protein–coupled receptors (GPCRs) remain primary therapeutic targets for numerous cardiovascular disorders, including heart failure (HF), because of their influence on cardiac remodeling in response to elevated neurohormone signaling. GPCR blockers have proven to be beneficial in the treatment of HF by reducing chronic G protein activation and cardiac remodeling, thereby extending the lifespan of patients with HF. Unfortunately, this effect does not persist indefinitely, thus next-generation therapeutics aim to selectively block harmful GPCR-mediated pathways while simultaneously promoting beneficial signaling. Transactivation of epidermal growth factor receptor (EGFR) has been shown to be mediated by an expanding repertoire of GPCRs in the heart, and promotes cardiomyocyte survival, thus may offer a new avenue of HF therapeutics. However, GPCR-dependent EGFR transactivation has also been shown to regulate cardiac hypertrophy and fibrosis by different GPCRs and through distinct molecular mechanisms. Here, we discuss the mechanisms and impact of GPCR-mediated EGFR transactivation in the heart, focusing on angiotensin II, urotensin II, and β-adrenergic receptor systems, and highlight areas of research that will help us to determine whether this pathway can be engaged as future therapeutic strategy.